The Effect of Smart Monitoring System on Attitudes and Adherences of Consuming Iron Supplement Tablets in Pregnant Women - Irdianty, Mellia Silvy; Maharani, Dian Ayu; Mustikarani, Innez Karunia (PT Inovasi Pratama Internasional, 2025)
Anemia is a condition of hemoglobin or red blood cells below 7gr/dl. The government's efforts to encourage pregnant women to consume 90 Fe tablets during pregnancy have not achieved national coverage due to the absence of a monitoring and evaluation program that is direct to low attitudes and adherence. Therefore, it is necessary to design an effective strategy with a smart monitoring system to observe the attitudes and adherence of pregnant women in consuming Fe tablets. The study aimed to determine the effect of a smart monitoring system on attitudes and adherence to the consumption of iron supplement tablets in pregnant women in the work area of Puskesmas Klego 1.The type of research adopted quantitative with the pre-experimental method using the one-group pre-test and post-test design research design. The sampling used a total sampling technique with 50 respondents. Data analysis utilized paired T-test and Wilcoxon test to determine the effect of a smart monitoring system on attitudes and adherence.The analysis of the Paired T-Test presented p value = 2.61 (p = 2.61->0.05). It indicated no effect of the smart monitoring system on attitudes. The results of the Wilcoxon test analysis obtained a p-value = 0.000 (p = 0.00-<0.05. There are differences in the effect of using the smart monitoring system on the attitudes of pregnant women in the work area of Puskesmas Klego 1. Recommendations for further research are to enhance the application features.